NOX emission analysis according to after-treatment devices (SCR, LNT + SCR, SDPF), and control strategies in Euro-6 light-duty diesel vehicles - Kim, Hyung Jun; Jo, Seongin; Kwon, Sangil; Lee, Jong-Tae; Park, Suhan (Fuel (Guildford), 2022)
•Since 2018, NOx of 132 Euro-6 LDVs certified in Korea was studied.•NOx according to after-treatment devices and control strategies was analyzed.•Accelerator pedal operation and EGR ratio have a direct impact on NOx.•In acceleration condition, the fuel amount and λ signal affect to NOx emission. This study used emission certification data for vehicles that met Korea's Euro-6 emission standards after 2018. It was analyzed that the distribution of nitrogen oxide (NOX) emission in accordance with the type of after-treatment system under cold and hot start conditions by classifying domestic and imported cars. In addition, the relationship between electronic control unit (ECU)/dosing control unit (DCU) signals and exhaust emissions were analyzed under NEDC and WLTP driving mode conditions. Three models of vehicles equipped with different after-treatment systems were selected among the vehicles subject to the 2019 real road driving test for this study. And it was acquired that ECU and DCU signals, which are expected to be related to emissions as well as emissions. In order to satisfy Euro-6, the LNT + SCR after-treatment system was applied to more than 76% of vehicle models. Among ECU signals, there was a direct relationship between the accelerator pedal and the EGR valve opening degree, and there was a deviation depending on the driving mode. Among the DCU signals, the catalyst temperature, urea-water injection quantity, and injection timing are controlled in accordance with the NOX emission measured by the sensor. In the future, it is necessary to analyze the correlation between the ECU signal and the DCU signal to derive a factor that can be used as a measure to suspect defeat devices.